Cellulose composite film and preparation process thereof

By introducing components such as MXene, AgNWs and hollow Fe3O4 into the cellulose composite film, the double-gradient structure composite film was prepared, which solved the problem of insufficient electromagnetic shielding ability and thermal conductivity of the cellulose composite film, and achieved efficient electromagnetic shielding and thermal conductivity. promote.

CN119119588APending Publication Date: 2024-12-13NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411240953.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing cellulose composite films have poor electromagnetic shielding and thermal conductivity, and cannot achieve continuous reflection and absorption, and cannot build a three-dimensional thermal conductivity network path.

Method used

Using composite films including 2-dimensional MXene, one-dimensional AgNWs, 0-dimensional hollow Fe3O4, cellulose nanofiber gel and other components, titanium carbide, silver nanowires, hollow iron tetroxide, and through layer-by-layer vacuum assisted suction filtration The process is used to prepare a double-gradient structure composite film to form good layer-to-layer binding effect and interaction between multi-dimensional particles.

Benefits of technology

The electromagnetic shielding ability and thermal conductivity are enhanced, the shielding efficiency reaches 45.8dB, the thermal conductivity can reach up to 2.92W/(m·K), and a good three-dimensional thermal conductivity network path is built through full mixing between multi-dimensional particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119588A_ABST
    Figure CN119119588A_ABST
Patent Text Reader

Abstract

The invention discloses a cellulose composite film and a preparation process thereof, and relates to the technical field of composite film preparation. The composite material is prepared from two-dimensional MXene, one-dimensional AgNWs, CNF, 0-dimensional hollow Fe3O4, titanium aluminum carbide, cellulose nanofiber gel, silver nitrate, lithium fluoride, concentrated hydrochloric acid, ethylene glycol, ferric chloride hexahydrate, polyvinylpyrrolidone, sodium acetate, acetone and absolute ethyl alcohol. Titanium carbide, silver nanowires and hollow ferroferric oxide are prepared, the MXene / AgNWs / Fe3O4 / CNF composite thin film with the double-gradient structure is finally prepared, the asymmetric gradient structure enables incident electromagnetic waves to achieve continuous reflection and absorption, the electromagnetic shielding capacity of the composite thin film is greatly enhanced, meanwhile, the absorption coefficient A of incidence on the low-conductivity side reaches 0.21, the shielding effectiveness reaches 45.8 dB, and the electromagnetic shielding performance of the composite thin film is greatly improved. Based on full mixing of multi-dimensional particles, a good three-dimensional heat conduction network path is constructed, the smaller the gradient difference between two adjacent layers in the gradient structure is, the higher the heat conductivity is, the highest heat conductivity of the material can reach 2.92 W / (m.K), and therefore the heat conduction performance of the gradient film is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite film preparation, in particular to a cellulose composite film and a preparation process thereof. Background Art

[0002] The development of 5G communication technology and electronic devices has brought great convenience to our daily lives, but the high-power operation of electronic devices has caused a lot of electromagnetic wave pollution problems, which will not only seriously affect the working life of precision electronic equipment, but also cause great harm to human health; at the same time, as electronic equipment develops towards high integration and miniaturization, it is bound to bring more serious problems such as heat accumulation. Therefore, in order to effectively dissipate heat and eliminate electromagnetic wave pollution problems, it is urgent to manufacture composite film materials with high thermal conductivity and strong absorption and electromagnetic shielding properties;

[0003] However, the cellulose composite film prepared by the prior art still has some defects:

[0004] The gradient structures of the cellulose composite films prepared by the prior art are mostly unable to achieve continuous reflection and absorption, resulting in poor electromagnetic shielding ability of the cellulose composite films. At the same time, the cellulose composite films are unable to construct a three-dimensional heat conduction network path, resulting in poor thermal conductivity of the cellulose composite films.

[0005] In view of the above problems, the inventors proposed a cellulose composite film and a preparation process thereof to solve the above problems. Summary of the invention

[0006] In order to solve the problems of poor electromagnetic shielding ability and poor thermal conductivity of cellulose composite films, the purpose of the present invention is to provide a cellulose composite film and a preparation process thereof.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solution: a cellulose composite film, the cellulose composite film comprising the following components:

[0008] 2D MXene, 1D AgNWs, CNF and 0D hollow Fe3O4, titanium aluminum carbide, cellulose nanofiber gel, silver nitrate, lithium fluoride, concentrated hydrochloric acid, ethylene glycol, ferric chloride hexahydrate, polyvinyl pyrrolidone, sodium acetate, acetone and anhydrous ethanol.

[0009] The present invention also provides a process for preparing a cellulose composite film, comprising the following steps:

[0010] S1. Preparation of titanium carbide, silver nanowires, and hollow ferroferric oxide

[0011] A1: A single-layer titanium carbide (Ti3C2Tx MXene) was prepared by etching with a mixed solution of lithium fluoride and concentrated hydrochloric acid. 20 mL of 9 M concentrated hydrochloric acid was added to a polytetrafluoroethylene beaker, 2.0 g of lithium fluoride powder was added and stirred at 350 r / min for 0.5 h to prepare an etching solution. Subsequently, 1.0 g of titanium aluminum carbide was slowly added to the etching solution. The solution was stirred continuously at 350 r / min for 24 h at 35 °C. The etching suspension was centrifuged and washed several times, and ultrasonically treated in an ice water bath. The ultrasonic solution was centrifuged at 3500 r / min for 1 h, and the supernatant was collected to obtain a two-dimensional single-layer Ti3C2Tx.

[0012] A2: Silver nanowires (AgNWs) were prepared by the polyol method. 0.5 g of ferric chloride hexahydrate powder was dissolved in 20 mL of ethylene glycol and stirred to obtain a solution. 0.2 g of the solution and 0.8 g of polyvinyl pyrrolidone were dissolved in 40 mL of ethylene glycol, which was recorded as solution A. 0.86 g of silver nitrate powder was dissolved in 40 mL of ethylene glycol, which was recorded as solution B. After mixing and stirring solution A and solution B for 30 min, they were transferred to a 100 mL reactor and subjected to hydrothermal reaction at 160 ° C for 150 min. Finally, the product was fully washed by centrifugation with acetone and anhydrous ethanol, and vacuum dried to obtain AgNWs.

[0013] A3: Hollow ferroferric oxide (Fe3O4) was prepared by template method. 1.1 g ferric chloride hexahydrate, 4.0 g polyvinyl pyrrolidone and 3.0 g sodium acetate were slowly added to 40 mL ethylene glycol solution in several times, stirred evenly to form a mixed solution, and then transferred to a 100 mL reactor for hydrothermal reaction. The mixture was rinsed with anhydrous ethanol and deionized water for 3 times respectively, and vacuum dried to obtain hollow Fe3O4 particles.

[0014] S2. Preparation of gradient thin film

[0015] Gradient structure composite films were prepared by layer-by-layer vacuum-assisted filtration process;

[0016] First, 2 g of cellulose nanofiber gel (CNF 1.25 wt%) was diluted with deionized water to a CNF aqueous dispersion with a concentration of 2 mg / mL. Subsequently, different masses of MXene, AgNWs mixture (MXene: AgNWs = 2:1) and hollow Fe3O4 particles were dispersed in the CNF aqueous dispersion, ultrasonicated for 1 h, and stirred to obtain a uniform dispersion. The obtained dispersion was filtered on a filter membrane (pore size: 0.22 μm) to self-assemble into a composite hydrogel, and then filtered layer by layer to obtain a gradient structure composite hydrogel. Subsequently, it was vacuum dried at a pressure of 5 KPa and a temperature of 60°C, and carefully peeled off from the filter membrane to obtain a dual gradient structure MXene / AgNWs / Fe3O4 / CNF composite film.

[0017] Preferably, in A1 of S1, the etching suspension is centrifuged at a speed of 3500 r / min for 2 min, the pH value of the etching suspension is 6, and the ultrasonic treatment time of the etching suspension is 1 h.

[0018] Preferably, in A2 of S1, the vacuum drying temperature for obtaining AgNWs is 50° C., and the vacuum drying time is 12 h.

[0019] Preferably, in A3 of S1, the temperature of the hydrothermal reaction is 200° C., the time of the hydrothermal reaction is 12 h, and the time of the vacuum drying is 12 h.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. In the present invention, titanium carbide, silver nanowires, and hollow ferroferric oxide are prepared, and finally a dual-gradient structure MXene / AgNWs / Fe3O4 / CNF composite film is prepared. The interaction between MXene, CNF, Fe3O4 and AgNWs reduces the agglomeration of AgNWs and Fe3O4, so that AgNWs and Fe3O4 are evenly distributed in the film. Due to the good adhesion of CNF and the large number of hydroxyl groups on the surface, a hydrogen bond structure is formed between the layers, forming a good bonding effect. Through the interaction between multiple and multi-dimensional particles, there is no obvious gap or void between the layers, and the bonding effect between the layers is good;

[0022] 2. In the present invention, titanium carbide, silver nanowires, and hollow ferroferric oxide are prepared, and finally a dual-gradient structure MXene / AgNWs / Fe3O4 / CNF composite film is prepared. Its asymmetric gradient structure enables the incident electromagnetic wave to achieve continuous reflection and absorption, thereby enhancing its electromagnetic shielding capability;

[0023] 3. In the present invention, titanium carbide, silver nanowires, and hollow ferroferric oxide are prepared, and finally a dual-gradient structure MXene / AgNWs / Fe3O4 / CNF composite film is prepared. The absorption coefficient A incident on the low conductivity side reaches 0.21, and the shielding effectiveness reaches 45.8 dB. Based on the full mixing between multi-dimensional particles, a good three-dimensional thermal conductive network pathway is constructed. As the gradient difference between two adjacent layers in the gradient structure becomes smaller, the thermal conductivity becomes higher. The thermal conductivity of the material can reach up to 2.92 W / (m·K), thereby improving the thermal conductivity of the gradient film. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 These are the SEM of Ti3AlC2, TEM of Ti3C2Tx, before and after MXene etching, and X-ray diffraction spectra of the present invention, as well as the SEM of AgNWs, TEM of AgNWs, and XPS full spectra before and after MXene etching.

[0026] Figure 2 The fracture SEM of CNF of the present invention, the fracture SEM of MXene + AgNWs (25-25-25) / Fe3O4 (25-25-25) / CNF, the fracture SEM of MXene + AgNWs (10-25-40) / Fe3O4 (40-25-10) / CNF, and the fracture Ti, Fe, and Ag element energy spectra of MXene + AgNWs (10-25-40) / Fe3O4 (40-25-10) / CNF;

[0027] Figure 3 EMI SE of the dual gradient film of the present invention, SE of different incident directions R , SE A , SE T , R, A at different incident directions, EMI SE of homogeneous Fe3O4 / conductive gradient film and double gradient film, SE at different incident directions R , SE A , SE T ,Schematic diagram of R and A under different incident directions;

[0028] Figure 4 Schematic diagram of the electromagnetic shielding mechanism of the double gradient film of the present invention;

[0029] Figure 5 is the thermal conductivity of the electromagnetic dual gradient film of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example: Figure 1-5 As shown, the present invention provides a cellulose composite film, the cellulose composite film comprising the following components:

[0032] 2D MXene, 1D AgNWs, CNF and 0D hollow Fe3O4, titanium aluminum carbide, cellulose nanofiber gel, silver nitrate, lithium fluoride, concentrated hydrochloric acid, ethylene glycol, ferric chloride hexahydrate, polyvinyl pyrrolidone, sodium acetate, acetone and anhydrous ethanol.

[0033] The present invention also provides a process for preparing a cellulose composite film, comprising the following steps:

[0034] S1. Preparation of titanium carbide, silver nanowires, and hollow ferroferric oxide

[0035] A1: A single-layer titanium carbide (Ti3C2Tx MXene) was prepared by etching with a mixed solution of lithium fluoride and concentrated hydrochloric acid. 20 mL of 9 M concentrated hydrochloric acid was added to a polytetrafluoroethylene beaker, 2.0 g of lithium fluoride powder was added and stirred at 350 r / min for 0.5 h to prepare an etching solution. Subsequently, 1.0 g of titanium aluminum carbide was slowly added to the etching solution. The solution was stirred continuously at 350 r / min for 24 h at 35 ° C. The etching suspension was centrifuged and washed several times. The etching suspension was centrifuged at a speed of 3500 r / min for 2 min to a pH value of 6. The solution was ultrasonically treated in an ice water bath for 1 h. The ultrasonic solution was centrifuged at 3500 r / min for 1 h. The supernatant was collected to obtain a two-dimensional single-layer Ti3C2Tx.

[0036] A2: Silver nanowires (AgNWs) were prepared by the polyol method. 0.5 g of ferric chloride hexahydrate powder was dissolved in 20 mL of ethylene glycol and stirred to obtain a solution. 0.2 g of the solution and 0.8 g of polyvinyl pyrrolidone were dissolved in 40 mL of ethylene glycol, which was recorded as solution A. 0.86 g of silver nitrate powder was dissolved in 40 mL of ethylene glycol, which was recorded as solution B. After mixing and stirring solution A and solution B for 30 min, they were transferred to a 100 mL reactor and subjected to hydrothermal reaction at 160 ° C for 150 min. Finally, the product was fully washed by centrifugation with acetone and anhydrous ethanol, and vacuum dried at 50 ° C for 12 h to obtain AgNWs.

[0037] A3: Hollow ferroferric oxide (Fe3O4) was prepared by template method. 1.1 g ferric chloride hexahydrate, 4.0 g polyvinyl pyrrolidone and 3.0 g sodium acetate were slowly added to 40 mL ethylene glycol solution in several times, stirred evenly to form a mixed solution, and then transferred to a 100 mL reactor for hydrothermal reaction at a temperature of 200 ° C for 12 h. The mixture was rinsed with anhydrous ethanol and deionized water for 3 times respectively, and vacuum dried for 12 h to obtain hollow Fe3O4 particles.

[0038] S2. Preparation of gradient thin film

[0039] Gradient structure composite films were prepared by layer-by-layer vacuum-assisted filtration process;

[0040] First, 2 g of cellulose nanofiber gel (CNF 1.25 wt%) was diluted with deionized water to a CNF aqueous dispersion with a concentration of 2 mg / mL. Subsequently, different masses of MXene, AgNWs mixture (MXene: AgNWs = 2: 1) and hollow Fe3O4 particles were dispersed in the CNF aqueous dispersion, ultrasonicated for 1 h, and stirred to obtain a uniform dispersion. The obtained dispersion was filtered on a filter membrane (pore size: 0.22 μm) to self-assemble into a composite hydrogel, and then filtered layer by layer to obtain a gradient structure composite hydrogel. Subsequently, it was vacuum dried at a pressure of 5 KPa and a temperature of 60 ° C, and carefully peeled off from the filter membrane to obtain a dual gradient structure MXene / AgNWs / Fe3O4 / CNF composite film. The detailed composition of the prepared gradient composite film is shown in Table 1:

[0041]

[0042] Through the above preparation process, the structure and composition of Ti3C2Tx MXene and AgNWs;

[0043] Single-layer Ti3C2Tx was prepared by selective chemical etching with lithium fluoride / concentrated hydrochloric acid. Figure 1 (a) is a scanning electron microscope (SEM) image of the raw material Ti3AlC2. After etching and peeling, the Al layer in the MAX phase is etched to form an accordion layered structure, which is then peeled off by ultrasonic centrifugation as shown in FIG. Figure 1 (b) The thin and large single-layer structure in the transmission electron microscopy (TEM) spectrum. Subsequently, the Ti3AlC2 before and after etching was analyzed by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), as shown in Figure 2. Figure 1 As shown in XRD of (c), after chemical etching, the (002) peak at 9.52° is reduced and shifted to 6.95°, and the (004), (101), (103), (104), and (105) crystal planes disappear, indicating that the interlayer spacing of the material increases. At this time, the Al layer in the MAX phase is successfully etched, while Figure 1 In (f) XPS, the disappearance of Al 2p and Al 2s in Ti3C2Tx indicates that the Al layer was successfully etched, while the newly appeared F1s indicates that -F functional groups were added to the surface of Ti3C2Tx during the etching process. One-dimensional AgNWs were prepared by the polyol method, such as Figure 1 As shown in (d) and (e), AgNWs with a diameter of about 100 nm and a length of 2-3 μm were prepared in a reactor by hydrothermal reaction.

[0044] Gradient structure MXene / AgNWs / Fe3O4 / CNF composite film morphology and structure;

[0045] The gradient structure composite film was prepared by a layer-by-layer vacuum-assisted filtration process. High-content conductive particles MXene and AgNWs (MXene: AgNWs = 2: 1), magnetic hollow Fe3O4 particles and CNF were ultrasonically mixed and first vacuum filtered. After the water was drained, the second layer was filtered according to the quality in Table 1. After three layers of filtration, the gradient mixed hydrogel was hot-pressed and dried.

[0046] from Figure 2 In (a), the composite film obtained by vacuum filtration with CNF as the matrix has good flexibility, and there are no obvious defects such as pores at the interface fracture; Figure 2 In (bc), due to the van der Waals interaction and two-dimensional lamellar structure of MXene, the mixed solution self-stacked during the filtration process to form a uniform lamellar structure. The interaction between MXene, CNF, Fe3O4 and AgNWs greatly reduced the agglomeration of AgNWs and Fe3O4, making AgNWs and Fe3O4 evenly distributed in the film. Figure 2 (d) The energy spectrum clearly shows a three-layer structure in which the Ti and Ag contents decrease layer by layer and the Fe content increases layer by layer. Due to the good adhesion of CNF and the large number of hydroxyl groups on the surface, a hydrogen bond structure is formed between the layers, resulting in a good bonding effect. Through the interaction between multiple and multi-dimensional particles, there is no obvious gap or void between the layers, and the bonding effect between the layers is good.

[0047] Electromagnetic shielding performance of gradient films;

[0048] Since precision instruments are affected by electromagnetic waves for a long time, the accuracy of the instruments will be seriously damaged and the service life of the instruments will be reduced. Therefore, MXene+AgNWs (MXene:AgNWs=2:1) ​​and Fe3O4 with different mass fractions were used as fillers to prepare composite films with gradient structures by layer-by-layer filtration to improve this phenomenon. Figure 3 (ac) is the study of the electromagnetic shielding performance of the conductive / magnetic-double gradient film. Figure 3 (a) It can be seen that compared with the highest EMI SE of 35.1dB in the homogeneous film, the gradient structure can effectively improve the electromagnetic shielding effectiveness of the material, and with the increase of the mass gradient between the two layers, the shielding effectiveness of the material gradually increases. When the conductive and magnetic gradients between the two layers are both 25mg, the shielding effectiveness reaches 45.8dB;

[0049] Subsequently, the shielding performance of the dual gradient film was compared under different incident directions. Changing the incident direction will affect the film's absorption coefficient of electromagnetic waves.A , A are both greater than the incident on the high conductivity and low magnetism side, while SE R , R is the opposite, which shows that changing the incident direction will effectively change the propagation path of the electromagnetic wave. When the electromagnetic wave is incident on the low-conductivity and high-magnetism side, the incident electromagnetic wave first contacts the absorption layer. Due to the good impedance matching characteristics, the electromagnetic wave can better enter the shielding material. When it is incident on the high-conductivity side, due to the serious impedance mismatch, the content of electromagnetic waves reflected on the surface is aggravated, which affects the material's absorption performance of electromagnetic waves. When the gradient structure is MXene+AgNWs(0-25-50)-Fe3O4(50-25-0), the absorption coefficient A incident on the low-conductivity side reaches 0.21, while the absorption coefficient A incident on the high-conductivity side is only 0.05, and the difference between the two is 0.16;

[0050] The MXene+AgNWs(10-25-40) / Fe3O4(40-25-10) / CNF conductive / magnetic-double gradient film and the MXene+AgNWs(10-25-40) / Fe3O4(25-25-25) / CNF conductive-single gradient film were analyzed separately. Figure 3 (df) It can be seen that the shielding structure with both electric / magnetic-dual gradient structure can alleviate the impedance mismatch problem between the incident electromagnetic wave and the composite film, allowing as many electromagnetic waves as possible to enter the composite film for dissipation and attenuation. The absorption efficiency of low conductivity incident is better than that of high conductivity incident, and the absorption efficiency of low conductivity incident in the dual gradient is the best, reaching 99.45%;

[0051] According to the experimental results, the shielding mechanism of the gradient structure is studied. The electromagnetic wave is incident on the side with high magnetism and low conductivity. Based on the good impedance matching of the absorption layer, most of the electromagnetic waves enter the shielding material, and only a small part of the electromagnetic waves are reflected. Some of the electromagnetic waves that enter the film are dissipated by magnetic loss in the absorption layer; the remaining electromagnetic waves enter the transition layer, and due to the increased conductivity of the transition layer, some of the electromagnetic waves are reflected and re-enter the absorption layer to be absorbed; then, the electromagnetic waves enter the reflection layer, and based on the high conductivity of the reflection layer, most of the electromagnetic waves are reflected, enter the transition layer, and gradually dissipate. Due to the stacked structure of the sheets obtained by vacuum filtration, the electromagnetic waves are dissipated by multiple reflections in the film, achieving the effect of electromagnetic shielding. Its asymmetric gradient structure enables the incident electromagnetic waves to achieve continuous reflection and absorption, greatly enhancing its electromagnetic shielding capability.

[0052] Thermal conductivity of gradient films;

[0053] The thermal conductivity of pure CNF film is 1.3W / (m·K). After adding 2D MXene, 1D thermally conductive particles AgNWs and 0D magnetic particles Fe3O4 to the system, due to the large amount of hydroxyl groups on the surface of CNF, CNF and other thermally conductive particles form hydrogen bonds during the uniform mixing process. Subsequently, vacuum-assisted filtration is used to stack the 2D lamellar structure, making the fillers tightly bonded. The 2D MXene, 1D AgNWs, CNF and 0D Fe3O4 multi-dimensional fillers are mixed and connected to each other, which greatly reduces the interfacial thermal resistance of the film, thereby building a good 3D thermal conductive network pathway, which improves the thermal conductivity of the material. The thermal conductivity of the material can reach up to 2.92W / (m·K), which is 2.25 times that of pure CNF film. At this time, MXene, AgNWs and Fe3O4 particles in the gradient structure are uniformly present in the system, and as the gradient difference between adjacent layers increases, the thermal conductive filler is unevenly distributed, and the thermal conductivity decreases compared to the homogeneous structure.

[0054] Taking CNF as the matrix, conductive particles MXen, AgNWs and magnetic hollow Fe3O4 particles were introduced as fillers, and a three-layer electromagnetic double gradient structure MXene / AgNWs / Fe3O4 / CNF composite film was prepared by vacuum assisted filtration. The self-stacking phenomenon of the two-dimensional layered structure MXene and the large amount of hydroxyl groups and adhesion on the CNF surface make the prepared composite film have good flexibility and film-forming properties. Based on the full mixing between multi-dimensional particles, a good three-dimensional thermal conductive network pathway is constructed. As the gradient difference between two adjacent layers in the gradient structure becomes smaller, the thermal conductivity increases. The thermal conductivity of the material can reach up to 2.92W / (m·K).

[0055] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A cellulose composite film, characterized in that The cellulose composite film comprises the following components: 2D MXene, 1D AgNWs, CNF and 0D hollow Fe3O4, titanium aluminum carbide, cellulose nanofiber gel, silver nitrate, lithium fluoride, concentrated hydrochloric acid, ethylene glycol, ferric chloride hexahydrate, polyvinyl pyrrolidone, sodium acetate, acetone and anhydrous ethanol.

2. A process for preparing the cellulose composite film according to claim 1, characterized in that: The following steps are involved: S1. Preparation of titanium carbide, silver nanowires, and hollow ferroferric oxide A1: A single-layer titanium carbide (Ti3C2Tx MXene) was prepared by etching with a mixed solution of lithium fluoride and concentrated hydrochloric acid. 20 mL of 9 M concentrated hydrochloric acid was added to a polytetrafluoroethylene beaker, 2.0 g of lithium fluoride powder was added and stirred at 350 r / min for 0.5 h to prepare an etching solution. Subsequently, 1.0 g of titanium aluminum carbide was slowly added to the etching solution. The solution was stirred continuously at 350 r / min for 24 h at 35 °C. The etching suspension was centrifuged and washed several times, and ultrasonically treated in an ice water bath. The ultrasonic solution was centrifuged at 3500 r / min for 1 h, and the supernatant was collected to obtain a two-dimensional single-layer Ti3C2Tx. A2: Silver nanowires (AgNWs) were prepared by the polyol method. 0.5 g of ferric chloride hexahydrate powder was dissolved in 20 mL of ethylene glycol and stirred to obtain a solution. 0.2 g of the solution and 0.8 g of polyvinyl pyrrolidone were dissolved in 40 mL of ethylene glycol, which was recorded as solution A. 0.86 g of silver nitrate powder was dissolved in 40 mL of ethylene glycol, which was recorded as solution B. After mixing and stirring solution A and solution B for 30 min, they were transferred to a 100 mL reactor and subjected to hydrothermal reaction at 160 ° C for 150 min. Finally, the product was fully washed by centrifugation with acetone and anhydrous ethanol, and vacuum dried to obtain AgNWs. A3: Hollow ferroferric oxide (Fe3O4) was prepared by template method. 1.1 g ferric chloride hexahydrate, 4.0 g polyvinyl pyrrolidone and 3.0 g sodium acetate were slowly added to 40 mL ethylene glycol solution in several times, stirred evenly to form a mixed solution, and then transferred to a 100 mL reactor for hydrothermal reaction. The mixture was rinsed with anhydrous ethanol and deionized water for 3 times respectively, and vacuum dried to obtain hollow Fe3O4 particles. S2. Preparation of gradient thin film Gradient structure composite films were prepared by layer-by-layer vacuum-assisted filtration process; First, 2 g of cellulose nanofiber gel (CNF 1.25 wt%) was diluted with deionized water to a CNF aqueous dispersion with a concentration of 2 mg / mL. Subsequently, different masses of MXene, AgNWs mixture (MXene: AgNWs = 2:1) and hollow Fe3O4 particles were dispersed in the CNF aqueous dispersion, ultrasonicated for 1 h, and stirred to obtain a uniform dispersion. The obtained dispersion was filtered on a filter membrane (pore size: 0.22 μm) to self-assemble into a composite hydrogel, and then filtered layer by layer to obtain a gradient structure composite hydrogel. Subsequently, it was vacuum dried at a pressure of 5 KPa and a temperature of 60°C, and carefully peeled off from the filter membrane to obtain a dual gradient structure MXene / AgNWs / Fe3O4 / CNF composite film.

3. A process for preparing a cellulose composite film according to claim 2, characterized in that: In A1 of S1, the etching suspension is centrifuged at a speed of 3500 r / min for 2 min, the pH value of the etching suspension is 6, and the ultrasonic treatment time of the etching suspension is 1 h.

4. A process for preparing a cellulose composite film according to claim 2, characterized in that: In A2 of S1, the vacuum drying temperature of AgNWs was 50°C and the vacuum drying time was 12 h.

5. The process for preparing a cellulose composite film according to claim 2, characterized in that: In A3 of S1, the temperature of the hydrothermal reaction is 200°C, the time of the hydrothermal reaction is 12 hours, and the time of the vacuum drying is 12 hours.